SCREENING OF WILD AND CULTIVATED SPECIES OF POTATO FOR FROST TOLERANCE IN NORTH-CENTRAL PLAINS OF INDIA - Luthra, S. K.; Gopal, J; Manivel, P.; Kumar, Vinod; Singh, B. P.; Pandey, S K. (Potato Journal, 2013)
One hundred nineteen accessions of 24 wild and cultivated species of potato were screened for frost tolerance and 18 accessions viz., SS 1636-3, 1660-4, 1724-1, 1725-22, 1725-43, 1725-44, 1725-70, 1725-74, 1725-76, 1725-78, 1725-93, 1732-8, 1770-11, 1780-3, 2040, 2038-5, 2040-13 and 2044-1 were found frost tolerant. Species S. spegazzinii (diploid) S. demissum (hexaploid) and S. tuberosum ssp. andigena (tetraploid) were found promising for frost tolerance.